Development of a collaborative tool for data valorisation in SMEs. Issue 10 (2022) - Toumelin, A.; Agard, B.; Leduc, M.
Abstract: In recent years, solutions based on Industry 4.0. technologies have become more and more accessible for SMEs. As a result, better data collection strategies are being developed and an increase in available data has been observed. Furthermore, SMEs contribute largely to the GDP in certain industrial sectors such as the food industry, food services and the health sector. These SMEs are therefore naturally oriented towards Industry 4.0. solutions such as decentralized data collection and decision-making techniques. To an identical industrial sector, these SMEs can be considered a decentralized network of companies. There is interest in improving the overall performance of this type of network, while optimizing the individual performance of each company. In this paper, we propose a collaborative tool and a methodology to visualize and improve the performance of SME networks. The methodology is implemented through a case study in the agri-food sector in the Canadian forage industry. The collaborative platform that is developed enables a visualization of production performance, management techniques and the specific aspects of each individual company. Then, it proposes a methodology for the improvement of each company through best practices that are identified in similar contexts within the network.